Pengaruh Sumber Informasi terhadap Keputusan Pembelian pada PT. Bank Negara Indonesia (BNI) Syariah Cabang Palembang - Isnaini Asiati, Diah (Jurnal Ilmu Manajemen, 2013)
The problems of this research was there any significant effect of resources together and partially to the purchase decision at PT BNI Syari’ah Palembang Branch . The goal is to identify and analyze the effect of significant resources together and partially to the purchase decision at PT BNI Syari’ah Palembang Branch . This type of research is associative . There are five variables used , namely personal resources , commercial resources , public resources , sources ofexperience and purchasing decisions . The main data research is the primary data collected by questionnaire technique . Data were analyzed using multiple linear regression . The results of the analysis showed that , the variable private resources , commercial resources , public resources , and sources of experience together significantly influence purchasing decisions at. Bank BNI Syariah Branch Palembang . But only partially public resources that provide significant influence on consumer purchasing decisions at. Bank BNI Syariah Palembang .